Pay attenti[on] Please. - Beatrice, Luca; Canova, Gianni; Castro Flórez, Fernando; Collu, Cristiana; Fadda, Franco; Ruiz de Samaniego, Alberto (Nuoro : MAN (Museo d'Arte Provincia di Nuoro), 2001)
Sierra, Santiago ; Ocampo, Manuel ; Varejao, Adriana ; Serrano, Andres ; Morales, Arnaldo ; Brower, Steven ; Torres, Baltazar ; Casarino, Claudia ; Monge, Priscilla ; Okón, Yoshua ; Lauretta, Francesco ; Meese, Jonathan ; Buetti, Daniele ; Doherty, Willie ; Melis, Melkiorre ; Roig, Bernardi ; Marty, Enrique ; Pujol, Ernesto ; Gonnord, Pierre ; Chiesi, Andrea ; Olaf, Erwin ; Tschäpe, Janaina ; Sanchez Blanco, Domingo ; Cao, Paco ; Moffatt, Tracey ; Vece, Costa ; Picco, Gabriele ; Sachs, Tom ; Salvino, Andrea ; Almeida, Efraim
biog., ind. tent., gr. tent. p. 189-206
Engels & Italiaans
Pay attenti[on] please, MAN (Museo d'Arte Provincia di Nuoro) Nuoro, 18 luglio - 14 ottobre 2001
boek